Life Orientation and Academic Performance of Selected Students with Physical Disabilities - Diego, Arnel A.; Villegas, Roland D.; Olegario, Ma Lourdes P.; Resuello, Jobelle T. (Future Science / FSH-PH Publications, 2024)
Disabled individuals often spend their lives grappling with low levels of optimism and unmet needs. It has been widely accepted that people with disabilities generally have fewer educational opportunities and a lower quality of life than their non-disabled counterparts. This present study employs descriptive research to investigate the relationship between life orientation and academic performance among selected students with physical disabilities. The participants were chosen through purposive sampling, consisting of sixty-four respondents from selected schools in Manila. Data were collected using a survey instrument, The Life Orientation Test Revised (LOTR). The researcher utilized the Z-test, H- test, weighted mean, and ANOVA to identify differences in variables, and Pearson's r to explore relationships. The findings revealed that students with physical disabilities are optimistic individuals; they accept and confront their condition despite the inconveniences and pain it may cause. Moreover, the present study showed that the higher the level of life orientation, the better the academic performance. Therefore, there is a need for the educational system to consider the life orientation of students when developing new strategies and approaches to understanding and teaching students with physical disabilities.